Influence Giving Compensation Financial, Non-Financial Compensation, And Motivation Work To Spirit Work Employee Perum Damri Medan - Dea Valentina Situmorang; Dhita Adriani Rangkuti; Innocence Helvi Vera Sinaga; Viktor Uluan Banjar Nahor; Julian Markus Sitorus (CERED Indonesia Institute, 2022)
This study aims to seek and provide compensation, the amount of non-financial compensation, and work motivation related to the morale of the employees of Perum Damri Medan. In this study, a population of 125 employees and 95 as a sample used a simple random sampling technique to become respondents in this study. Therefore, quantitative and descriptive approach methods are methods that can provide an overview, with questionnaire and interview techniques as the initial stage. SPSS software becomes a tool to test somanalysesis. get the results Based on that financial compensation, non-financial compensation, and work motivation has a number greater than the partial provision of 1986 and simultaneously valued at 16,348 greater than, 2.70 and a significantly less than 0.05. So financial compensation, non-financial compensation spirit, and work motivation have a positive influence on employee work.